show that
tan48 tan23 tan 42 tan67 =1
Answers
Answered by
1
Hi Friend !!!
====================
tan 48 = cot 42
= 1/tan42
tan 23 = cot 67
= 1/tan 67
tan 48 tan 23 tan 42 tan 67 = 1
1/tan42 1/tan 67 tan 42 tan 67
= 1
Hope it helps u :-)
====================
tan 48 = cot 42
= 1/tan42
tan 23 = cot 67
= 1/tan 67
tan 48 tan 23 tan 42 tan 67 = 1
1/tan42 1/tan 67 tan 42 tan 67
= 1
Hope it helps u :-)
tejasri2:
plz brainliest if it helps u
Answered by
2
Tan 48 . Tan 23 . Tan 42. Tan 67 = l.h.s
Cot (90-48). Cot (90-23) . Tan 42 . Tan 67
Cot 42 . Cot 67. Tan 42 . Tan 67 = 1
We know that tan a. cot a = 1
R.h.s = 1
Hence proved......
Thank u★★★
#ckc
Cot (90-48). Cot (90-23) . Tan 42 . Tan 67
Cot 42 . Cot 67. Tan 42 . Tan 67 = 1
We know that tan a. cot a = 1
R.h.s = 1
Hence proved......
Thank u★★★
#ckc
Similar questions